ANALISIS PUBLIKASI DAN LAPORAN KEUANGAN LAZISMU BERDASARKAN PSAK NO. 45 (STUDI KASUS LAZISMU MENTENG JAKARTA PUSAT) - Agung Haryanto; Fatma Yeni (Ekonomi Islam, 2019)
This study aims to conduct an analysis related to the publication and preparation of financial statements of LAZISMU based on Statement of Financial Accounting Standards (PSAK) No. 45. The method used in this study is descriptive quantitative. Based on the results of the interview, it was reported that the financial statements were published in a comparative way, the aim being that users of financial statements could compare the performance of LAZISMU with the previous year. The researcher found that the annual report was still a general description related to the amount of fund distribution and the parties receiving the funds. Published reports should be in the form of nominal of each fund channeled. Furthermore, based on the explanation from the financial manager, it was stated that the financial statements of LAZISMU were no longer using PSAK No. 45 but have already switched to PSAK No. 109. This means that the preparation of financial statements of LAZISMU has used the most appropriate standard of preparation. Keyword: Financial Report, Zakat Institution, PSAK No.109